Standard blank for wood lamination on khaya ivorensis / Izzah Azimah Noh ...[et al.] - Noh, Izzah Azimah; Ahmad, Said; Awang, Khairul; Moh Yusoff, Muhammad Najib (2014)
This paper focuses on the standard blank for wood lamination on Khaya ivorensis. Standard blank is a cutting standard for a blank which are provides improving and increasing the value of sawn timber. Parameters for standard blank were machining practices and lamination process. Adhesives used for the study is Polyvinyl Acetate (PVAc). The purpose of standard blank based on machining practices (system) and lamination process (process). Explain that, the different machine used in producing sawn timber provides different result for surface roughness that affects the gluing properties during lamination process. The physical and mechanical properties were tested as Modulus of Rupture (MOR), Modulus 0f Elasticity (MOE), Compression shear and Delamination test were evaluated based on reference standard of in house method testing; BS 373:2008 (MOR and MOE), BS 373:1957- reconfirm 2008 (Compression shear) and JAS 1751 2008 (Delamination test). For the system, there are two type of system; sanding system (S1) and without sanding system (S2). Overall results show that the without sanding system is recommend in the production. Other than that, there are three type of lamination process that need to be compare for this study which are plane and plane (P1), rip and rip (P2) and plane and rip (P3). From the three type of lamination process, the most suitable surface used for lamination process by using different machining practices is plane and plane.